2014
DOI: 10.1007/s00702-014-1162-x
|View full text |Cite
|
Sign up to set email alerts
|

Altered peripheral BDNF mRNA expression and BDNF protein concentrations in blood of children and adolescents with autism spectrum disorder

Abstract: Findings from molecular genetic studies and analyses of postmortem and peripheral tissue led to the hypothesis that neurotrophins-as crucial moderators of neuroplasticity-impact on the pathophysiology of autism spectrum disorder (ASD). The study projects aimed to complement former results on the role of brain-derived neurotrophic factor (BDNF), a member of the neurotrophin family with fundamental impact on brain development and function. The purpose of this work was to investigate peripheral BDNF mRNA expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 77 publications
1
34
0
Order By: Relevance
“…Serum levels of BDNF mRNA and BDNF protein are overall lower in patients with autism (49) and serum BDNF mRNA levels may positively correlate with IQ in patients with ASD (49). A crucial experiment by Lauterborn et al (44) showed that impaired LTP (long term potentiation) in the Fmr1-KO mouse model is rescued when hippocampal slices are bathed in BDNF.…”
Section: Serotonin and Up-regulation Of Brain Derived Neurotropic Facmentioning
confidence: 99%
“…Serum levels of BDNF mRNA and BDNF protein are overall lower in patients with autism (49) and serum BDNF mRNA levels may positively correlate with IQ in patients with ASD (49). A crucial experiment by Lauterborn et al (44) showed that impaired LTP (long term potentiation) in the Fmr1-KO mouse model is rescued when hippocampal slices are bathed in BDNF.…”
Section: Serotonin and Up-regulation Of Brain Derived Neurotropic Facmentioning
confidence: 99%
“…Contradictory evidences support an association between BDNF expression and ASD [25][26][27][29][30][31][32]. Recently, peripheral mRNA expression of BDNF was analysed also in the whole blood searching for possible biologic markers for ASD [32].…”
Section: Discussionmentioning
confidence: 97%
“…Nevertheless, other authors reported decreased BDNF and NT3 levels in serum of autistic patients [30,31]. Regarding messenger RNA (mRNA) levels, more recent studies revealed a significant reduction in BDNF expression [32]. The diversity of hitherto existing results might be due to varying patient groups included, differences in analysed tissues and utilized methods as well as influences of cofactors such as age and puberty state [32].…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Studies have found reduced peripheral BDNF protein and mRNA levels in the blood of neonates (Abdallah et al, 2013), children, adolescents (Katoh-Semba et al, 2007;Taurines et al, 2014) and adults with ASDs (Hashimoto et al, 2006). In particular, KatohSemba and colleagues found when examining the early developmental profile of BDNF expression that in healthy controls, serum BDNF protein level increase over the first few years of development before plateauing at adulthood whereas in autism sufferers BDNF levels were significantly lower from the ages 0e9 years compared to teenage and adult patients as well as controls, strongly indicative of a delayed BDNF developmental trajectory (Katoh-Semba et al, 2007).…”
Section: Autismmentioning
confidence: 99%